Halide Perovskite Excitonic Diffraction Grating. Issue 5 (22nd December 2022) - Mamaeva, Mariia P.; Lozhkin, Maksim S.; Shurukhina, Anna V.; Stroganov, Boris V.; Emeline, Alexei V.; Kapitonov, Yury V.
Abstract: Resonant diffractive optical elements can be used to create the desired spatial and angular distribution of scattered light in a narrow wavelength range. Exciton resonance could help to make such elements active. Here an exciton diffraction grating made from fully inorganic CsPbBr3 halide perovskite is demonstrated. Spatial modulation of excitonic properties of the single crystal is achieved using local defect formation by 30 keV Ga + focused ion irradiation with low irradiation dose 10 14  cm −2 . Such a low dose prevents the appearance of non‐resonant diffraction since no sample milling occurs. The observed diffraction reflex has a maximum efficiency of 2.3 × 10 −3 at the free exciton resonance and 1.7 meV spectral width. The temperature, angular, and spectral properties of resonant diffraction are studied. The possibility of creating exciton diffraction gratings based on halide perovskites is one more confirmation of their applicability as a new material for information photonics. Abstract : Diffractive optical element based on fully inorganic halide perovskite CsPbBr3 is demonstrated. Spatial modulation of excitonic properties of the single crystal is achieved using local defect formation by focused ion irradiation with a low irradiation dose, which prevents the appearance of non‐resonant diffraction since no sample milling occurs. The temperature, angular, and spectral properties of resonant diffraction are studied.